Red State Revolt: The Teachers’ Strikes and Working-Class Politics - Bennett, Michael (Radical Teacher, 2020)
A review of Eric Blanc's Red State Revolt: The Teachers’ Strikes and Working-Class Politics. NY: Verso, 2019.